2022
DOI: 10.3389/fendo.2022.925848
|View full text |Cite
|
Sign up to set email alerts
|

N-Butanol Extract of Modified You-Gui-Yin Attenuates Osteoclastogenesis and Ameliorates Osteoporosis by Inhibiting RANKL-Mediated NF-κB Signaling

Abstract: Postmenopausal Osteoporosis (PMOP) is the most prevalent primary osteoporosis, attributable to an imbalance in osteoblast and osteoclast activity. Modified You-Gui-Yin (MYGY), a traditional Chinese herbal formula, is able to effectively treat PMOP, while the critical components and pharmacological mechanisms of MYGY are still unclear. In this study, we aimed to investigate the therapeutic effects and underlying mechanisms of N-butanol extract of MYGY (MYGY-Nb) in ovariectomized (OVX)-induced osteoporosis mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…All these indicated that the female reproductive system especially the ovary is closely related to bone, and YGY can inhibit bone loss by promoting osteogenic proliferation and differentiation and attenuating osteoclastogenesis. [ 20 , 21 ] In western medicine, ONFH is a disease involving changes in local stem cell activity of the femoral head. [ 22 ] The researchers found a decrease in the number, activity, or osteogenic differentiation of mesenchymal stem cells in the bone marrow in patients with ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…All these indicated that the female reproductive system especially the ovary is closely related to bone, and YGY can inhibit bone loss by promoting osteogenic proliferation and differentiation and attenuating osteoclastogenesis. [ 20 , 21 ] In western medicine, ONFH is a disease involving changes in local stem cell activity of the femoral head. [ 22 ] The researchers found a decrease in the number, activity, or osteogenic differentiation of mesenchymal stem cells in the bone marrow in patients with ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…TCM formulas, BSHXD, and Jianpi Qingchang Bushen decoction (JQBD) can alleviate bone loss, decrease bone volume, and limit osteoclastogenesis by reducing the RANKL-stimulated NF-κB, ERK, JNK signal transduction pathways in OP model mice ( 93 , 98 ). Bushen Tongluo decoction (BSTLD) and You Gui Yin (YGY) can promote bone generation and attenuate OC activity and bone resorption in the OVX-induced OP mouse model by reducing RANKL/OPG ratio ( 53 , 99 ).…”
Section: Anti-op Effects Of Tcm and Plant-based Natural Compoundsmentioning
confidence: 99%
“…RANKL (osteoprotegerin ligand) activates the formation and activation of osteoclasts by binding to its receptor, thus promoting bone absorption. OPG (osteoprotegerin) is a natural antagonist of RANKL, which can bind to RANKL and prevent it from binding with RANKL, thus inhibiting bone resorption 6 . Activating the Wnt/β- catenin pathway can promote the proliferation and differentiation of osteoblasts and increase bone formation 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%